2020
DOI: 10.2147/ott.s237802
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA SNHG7 Functions as an Oncogene in Cervical Cancer by Sponging miR-485-5p to Modulate JUND Expression</p>

Abstract: Background: Long non-coding RNA (LncRNA) SNHG7 is involved in the development of multiple cancers. However, its role in cervical cancer (CC) has not been elucidated. This study aimed to explore the function of SNHG7 in CC progression and the underlying mechanisms. Materials and Methods: The expression levels of SNHG7 and miR-485-5p in CC tissues and cell lines were measured by qPCR. Functional experiments including CCK-8 assay, wound healing assay, transwell assay, flow cytometry, Western blot, luciferases rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Our study further demonstrated that the BMSC-derived EVs could transfer miR-375 to cervical cancer cells and consequently acted as antioncogene in cervical cancer cells, evidenced by promoted cell apoptosis and inhibited cell migration and invasion. Importantly, the inhibited proliferation, migration, and invasion are significant indicators for the amelioration of cervical cancer [ 30 , 31 ]. Moreover, the present study clarified that BMSC-derived EV-incorporated miR-375 could ameliorate cervical cancer progression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Our study further demonstrated that the BMSC-derived EVs could transfer miR-375 to cervical cancer cells and consequently acted as antioncogene in cervical cancer cells, evidenced by promoted cell apoptosis and inhibited cell migration and invasion. Importantly, the inhibited proliferation, migration, and invasion are significant indicators for the amelioration of cervical cancer [ 30 , 31 ]. Moreover, the present study clarified that BMSC-derived EV-incorporated miR-375 could ameliorate cervical cancer progression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the most widely studied latent mechanism of action of lncRNAs is based on the role of a ceRNA that sponges miRNAs to alleviate the repression of their target genes. [30][31][32] Following the identification of the expression profile and functions of RGMB-AS1 in GC, it was necessary to elucidate the mechanisms responsible for the oncogenic activities of RGMB-AS1 in GC progression. Accordingly, we demonstrated that RGMB-AS1, which harbors miR-574-binding sites, can act as an effective sponge toward miR-574, thereby positively modulating HDAC4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…ELK1 expression was restrained by OE miR-330-5p and facilitated by knockdown of miR-330-5p. 15 Furthermore, ELK1 has a target relationship with miR-185-5p. 23 The most glamorous finding was that elevated miR-130b-5p or silenced ELK1 inhibited self-renewal ability, stemness, colony formation, proliferation, migration, and invasion abilities, promoted apoptosis of CC stem cells, and decreased the weight and volume of tumor in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…But there were no concrete studies about the relationship between miR‐130b‐5p and CC. ETS transcription factor (TF) (ELK1) is a transcription activator that regulates various genes regarding proliferation and metastasis 15 . A study has revealed that ELK1‐activated GPC3‐AS1/GPC3 axis is beneficial for the progress of CC cells 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation